2018
DOI: 10.1093/cvr/cvy057
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cardiac Wnt/β-catenin signalling in desmoplakin-deficient AC8 zebrafish models is rescuable by genetic and pharmacological intervention

Abstract: Our data point to Wnt/β-catenin as the final common pathway underlying different desmosomal AC forms and support the zebrafish as a suitable model for detecting early signalling pathways involved in the pathogenesis of DSP-associated diseases, possibly responsive to pharmacological or genetic rescue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…Desmosomes also help localize the actin‐regulatory machinery including Rho‐GTPases, which might further impact the organisation and function of the adherens junctions associated actin cytoskeleton and contractile apparatus. Desmosome components also regulate multiple other signalling pathways including GSK3beta/Wnt, p38/TGFbeta and Ras/Erk2 . Coupling with these pathways regulates multiple endpoints in skin and heart, including cell fate, differentiation, and fibrotic gene expression.…”
Section: What Is the Role Of The Desmosome In Arrhythmogenic Cardiomymentioning
confidence: 99%
“…Desmosomes also help localize the actin‐regulatory machinery including Rho‐GTPases, which might further impact the organisation and function of the adherens junctions associated actin cytoskeleton and contractile apparatus. Desmosome components also regulate multiple other signalling pathways including GSK3beta/Wnt, p38/TGFbeta and Ras/Erk2 . Coupling with these pathways regulates multiple endpoints in skin and heart, including cell fate, differentiation, and fibrotic gene expression.…”
Section: What Is the Role Of The Desmosome In Arrhythmogenic Cardiomymentioning
confidence: 99%
“…Moreover, a zebrafish model of DSP deficiency has been recently generated for in vivo cell signaling screen, using pathway-specific reporter transgenes. Out of nine considered, three pathways (Wnt/β-catenin, TGFβ/Smad3, and Hippo/YAP-TAZ) were significantly altered, with Wnt as the most dramatically affected (Giuliodori et al, 2018). The findings of all these papers point to Wnt/β-catenin as the final common pathway underlying the ACM pathogenesis, independently from the causal gene.…”
Section: Wnt Signaling In Acm and Smdmentioning
confidence: 96%
“…AKT was found inhibited, leading to GSK-3β activation and consequent inhibition of β-catenin activity in this mouse model [ 23 ]. Furthermore, the pathogenic role of inhibition of Wnt signaling in ACM has been shown in an ACM transgenic mouse model with cardiomyocyte-specific overexpression of a FLAG-tagged human desmoglein-2 with the Q558* nonsense mutation [ 20 ] and in a zebrafish model of DSP deficiency [ 21 ]. Collectively, these results suggest that alteration of Wnt signaling pathway could be an important mechanism underlying the fibrofatty infiltration in both desmosomal and non-desmosomal ACM.…”
Section: Molecular Pathogenic Pathwaysmentioning
confidence: 99%
“…In addition, activation of the Hippo signaling was responsible for Wnt inactivation through sequestration of β-catenin in the cytosol by pYAP. A recent study on a novel zebrafish model of DSP deficiency has shown that Hippo/YAP-TAZ, Wnt/β-catenin and TGFβ/Smad3 were significantly altered [ 21 ]. The findings of these studies strongly indicate a mechanistic association among mutations in desmosomal components, Hippo pathway activation, Wnt inhibition and enhanced adipogenesis in ACM.…”
Section: Molecular Pathogenic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation